THE EVOLUTION OF DA'WAH MEDIA MANAGEMENT WITHIN ISLAMIC INSTITUTIONS IN INDONESIA: A HISTORICAL ANALYSIS AND ORGANIZATIONAL TRANSFORMATION - Faishal Sultan Bagaskara (Jurnal Manajemen Dakwah, 2026)
This study aims to analysis the evolution of Da'wah media management in Indonesia, from the use of manuscripts to the transition to the digital era. Da’wah media transformation is not simply a change in tools, but rather a fundamental transformation in the communication management strategies of da’wah institutions. Using literature study and historical analysis, this study explores how da'wah management has adapted to technological changes over time. The research findings indicate that da'wah media management has undergone three main stages of evolution: the elitist era of manuscripts and print literacy, the era of conventional broadcasting that expanded mass reach, and the interactive and decentralized digital era. This shift requires da'wah institutions to reorient their management, including more adaptive content planning, organizing technologically literate human resources, and controlling the quality of information amidst the flood of data. This article provides a theoretical contribution to the development of da'wah management by presenting a historically based media adaptation framework. The results of this analysis are expected to serve as a reference for da’wah institution management in developing relevant communication strategies amidst the sustain development dynamics of information technology.